Pengaruh Pemberian Ekstrak Jambu Biji (Psidium guajava) terhadap Daya Ikat Air, Susut Masak, Keempukan, dan pH Daging Ayam Petelur Afkir - Muhamad Teja Haikal; Lilis Suryaningsih; Eka Wulandari (Unpad Press, 2021)
Rejected laying hens meat are less attractive to the public, because it has a tough texture. Guava fruit (Psidium guajava) contains ascorbic acid which can be used as a meat tenderizer, therefore research was carried out to determine the effect of giving guava extract (Psidium guajava) to water holding capacity, cooking loss, tenderness and pH of rejected layer hens meat. The research has been carried out at the Laboratory of Animal Products Processing Technology, Faculty of Animal Husbandry, Padjadjaran University on March 2021. The research was conducted with experimen-tally methods using a completely randomized design (CRD) with 4 treatments is the immersion of guava extract with an amount of 20% (P1), 30% (P2), 40% (P3), 50% (P4). Immersion was carried out for 30 minutes with each treatment repeatition 5 times. The result of this research were giving guava extract with a concentration of 40% gave the best effect with using Duncan’s multiple rage test, with the value of water holding capacity 20,11 %, cooking loss 28,28 %, tenderness 30,28 mm/g/10 second and pH 6,64 on rejected layer hens meat.